Sistem Informasi Pengendalian Stok Bahan Baku Pada CV Style Promo Collection Dengan Menggunakan Metode Economic Order Quantity - Cahyono, Lukman Arief; Anita, Anita; Kanthi, Yekti Asmoro (LPPM STIKI MALANG, 2020)
Control of raw material stocks is very important in supporting the production process, however, if the control of raw material stocks is not properly controlled, it will have an impact on dead stock and shortages of raw materials which will result in delays in the production process and a decrease in the selling price of these materials. This problem is currently occurring at the CV Style Promo Collection, which is experiencing this problem and requires a system to help control raw material stocks so that the current problems can be resolved with the system to be created, to increase the level of success in controlling raw material stocks. The economic order quantity method is used in the process of calculating the number of raw materials that must be ordered at that time. From the creation of this new system, we can manage the stock of raw materials properly because the process of ordering raw materials has been determined by automatic calculation and there is information about stock safety and when to reorder.